Surgical outcomes of spinal cavernous malformations: A retrospective study of 98 patients - Liao, Dengyong; Wang, Ruoran; Shan, Baoyin; Chen, Haifeng (Frontiers in Surgery, 2023)
Abstract Objective: Spinal cord cavernous malformation (SCCM) is a rare vascular lesion, and the treatment strategy remains controversial at present. The goal of this retrospective study was to analyze the surgical outcomes of the SCCM and to find more appropriate treatment strategies for a better prognosis. Method: A retrospective review of 98 patients with SCCM from 2009 to 2018 was conducted at the neurosurgical center of our hospital. Neurological function was assessed using the American Spinal Injury Association (ASIA) impairment scale. Clinical features were analyzed using the multiple logistic regression. Results: Ninety-eight patients with SCCM were included, of whom 35.7% were female (n = 35) and 64.3% male (n = 63). The mean age was 41.6 years; and family history was reported in 8.2% of patients (n = 8). Definite hemorrhage was found in 6.1% (n = 6). Before surgery, the neurological status of patients was 2%, 2%, 12.2%, 54.1%, and 29.6% in Grade A (n = 2), B (n = 2), C (n = 12), D (n = 53), and E (n = 29), respectively. 82.7% (81/98) patients had long-term follow-up, of whom, 34 had improved, 41 were stable and 6 had deteriorated. Patients with dorsal or superficial lesions showed better improvement than those with ventral or lateral deep lesions. Those with symptoms lasting less than three months had higher rates of improvement than those with symptoms lasting more than three months. However, there was no significant difference in prognosis between hemilaminectomy and laminectomy. Conclusion: These results suggest that surgical strategies should be preferred for severe symptomatic SCCMs if total resection can be achieved, thereby avoiding the risk of severe complications with subsequent lesion hemorrhage. Earlier (usually within 3 months of symptom duration) surgical resection generally leads to a better prognosis. For asymptomatic SCCMs, however, which are particularly located deep in the ventral or lateral portions of the spinal cord, surgery can result in serious complications such as paralysis. As a result, conservative treatments may be selected based on rigorous follow-up.